The design, development and evaluation of RESAM Carving Kit / Noren Md Ali - Md Ali, Noren (Faculty of Education, 2014)
Very often, art teachers find it difficult to obtain relevant carving tools for their students. These tools are usually costly and difficult to obtain. Therefore, to help art teachers overcome the problem of getting the relevant carving tools, this RESAM Carving Kit was designed to provide an alternative tool for teaching carving as part of Visual Art Education syllabus. These carving tools are made from the twigs of Resam tree (Dicranopteris linearis). They are hard and durable which makes it easy to carry, cost effective and can be sharpened when blunt. This tree can also be found easily by the roadsides of the highway. The emphasis of the carving syllabus at the secondary school is more on the techniques and processes. Therefore, this RESAM Carving Kit can provide a good alternative for students to learn the carving techniques. Students and teachers can also make the carving tools themselves. These 10 pieces of RESAM Carving Kit are labelled individually with numbers for easy identification. These numbers signify the various shapes of each carving tool and the carving effect that it can produce. The carving points of each RESAM Carving Kit are shaped very similar to the metal carving tools used for wood carving. Although this was inspired by the manuscript pen, the researcher finds that it is a good invention and innovation in education as it provides good quality tool for carving. It is very easy to obtain and very practical. A study was done among art teachers and students in one of the schools in Shah Alam and the results showed that the students and teachers found the RESAM Carving Kit to be very helpful in the process of teaching and learning of carving.